Nitrogen-doped porous carbon composite material as well as preparation method and application thereof
By efficiently loading precious metals in nitrogen-doped porous carbon composite materials, the problems of low loading and poor dispersion of precious metals in the prior art are solved, and the resource utilization of waste plastics is realized, which improves the performance and application prospects of the catalyst.
Patent Information
- Application Number
- CN202411637976.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-28
AI Technical Summary
The existing carbon-loaded metal catalysts have low precious metal loads and poor dispersion, resulting in low catalytic performance, and difficulty in disposing of waste plastics, and lack effective resource reuse methods.
A nitrogen-doped porous carbon composite material is used as the catalyst substrate, and the waste plastic is reacted with the precious metal precursor through two heat treatment methods to prepare a high load and uniform dispersion precious metal catalyst.
It significantly improves the load and dispersion of precious metals, improves catalytic activity, realizes the resource reuse of waste plastics, and has a wide range of catalyst application prospects.
Smart Images

Figure CN119524901A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of carbon materials, and in particular to a nitrogen-doped porous carbon composite material and a preparation method and application thereof. Background Art
[0002] With the increasing global environmental protection requirements and the increasing shortage of resources, the development of low-cost, high-performance new catalytic materials has become an important research direction in many fields such as energy, environment, and chemical industry. Carbon-based materials have become a hot research topic in the field of catalysis due to their wide sources, low costs, and high specific surface area. Especially in the preparation of metal catalysts, carbon materials have become ideal carriers of metal active sites due to their good stability, conductivity, large specific surface area, and chemical adjustability. By loading metals onto carbon-based materials, the activity and selectivity of catalytic reactions can be effectively improved, especially in fuel cell catalysts, VOCs catalytic oxidation, and chemical material quality upgrades.
[0003] Common metal materials loaded on porous carbon surfaces include precious metals (such as Pt, Pd) and transition metals (such as Cu, Mn) and their oxides. However, existing carbon-supported metal catalysts still have two key limitations in improving catalytic performance. First, the amount of loaded metal is insufficient, especially for precious metal catalysts, whose expensive price makes their loading amount the main factor restricting the economic efficiency of the catalyst; second, the dispersion of the loaded metal is low, and the agglomeration or uneven distribution of metal particles will lead to the waste of active sites, thereby reducing the effectiveness and stability of the catalyst. Therefore, how to increase the loading amount and dispersion of metals, especially precious metals, on carbon materials has become an important topic in the field of catalyst research.
[0004] At the same time, a large amount of waste plastics are usually disposed of by landfill or incineration, but this treatment method also puts a great burden on the environment. Therefore, it is necessary to research and develop a new resource recycling method for waste plastics. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems of the prior art such as low precious metal loading and poor dispersibility and difficulty in resource recovery of waste plastics, and to provide a nitrogen-doped porous carbon composite material and a preparation method and application thereof. The nitrogen-doped porous carbon composite material has a high precious metal loading and significantly improves the dispersibility of the loaded precious metal, greatly improves the utilization efficiency of the loaded precious metal active sites, and improves the catalytic performance of the nitrogen-doped porous carbon composite material, so that it can be well used as a catalyst in the fields of fuel cells, electrocatalysis and VOCs catalytic oxidation.
[0006] In order to achieve the above object, the present invention provides a nitrogen-doped porous carbon composite material on one hand, wherein the nitrogen-doped porous carbon composite material comprises nitrogen-doped porous carbon and a noble metal element loaded on the nitrogen-doped porous carbon;
[0007] Wherein, the noble metal element is selected from one or more of Pt, Pd, Au, Ru and Ir;
[0008] The specific surface area of the nitrogen-doped porous carbon is 100-700 m2 / g, and the atomic percentage of nitrogen in the nitrogen-doped porous carbon is 3-6 at%;
[0009] In the nitrogen-doped porous carbon composite material, the loading amount of the noble metal element is 0.8-2.3 wt %.
[0010] A second aspect of the present invention provides a method for preparing a nitrogen-doped porous carbon composite material, the method comprising the following steps:
[0011] (1) crushing the waste plastic, and then mixing the obtained waste plastic particles with an optional nitrogen source for a heat treatment;
[0012] (2) mixing the product obtained by the heat treatment with a noble metal precursor solution, then drying the mixed solution, and then subjecting the obtained dry product to a secondary heat treatment;
[0013] The conditions of the primary heat treatment include: a temperature of 750-900°C and a time of 4-5h;
[0014] The conditions of the secondary heat treatment include: temperature of 650-850°C and time of 3.5-4.5h;
[0015] The waste plastic is selected from one or more of waste polyurethane plastic, waste polyamide plastic and waste polyimide plastic;
[0016] The noble metal precursor in the noble metal precursor solution is selected from at least one of a palladium precursor, a platinum precursor, a gold precursor, a ruthenium precursor and an iridium precursor.
[0017] Preferably, the particle size of the waste plastic particles is 10-150 μm.
[0018] Preferably, in step (1), the primary heat treatment is performed in an inert gas;
[0019] Preferably, the inert gas is selected from at least one of nitrogen, argon and helium;
[0020] Preferably, during the primary heat treatment, the ratio of the sum of the weights of the waste plastic particles and the nitrogen source to the flow rate of the inert gas is 1 g:90-110 mL / min.
[0021] Preferably, the weight ratio of the noble metal precursor to the waste plastic particles is 0.008-0.1:1.
[0022] Preferably, the nitrogen source is selected from one or more of urea, melamine and ethylenediaminetetraacetic acid.
[0023] Preferably, the weight ratio of the waste plastic particles to the nitrogen source is 1:0.1-0.5.
[0024] Preferably, during the primary heat treatment and the secondary heat treatment, the heating rate is 1-20° C. / min.
[0025] A second aspect of the present invention provides a nitrogen-doped porous carbon composite material prepared by the above method.
[0026] The third aspect of the present invention provides an application of the nitrogen-doped porous carbon composite material in the preparation of a fuel cell catalyst, a water electrolysis catalyst or a VOCs catalytic oxidation catalyst.
[0027] In the nitrogen-doped porous carbon composite material described in the present invention, nitrogen-doped porous carbon is used as a loading substrate, and precious metals show a higher metal loading amount and a more uniform metal distribution on the nitrogen-doped porous carbon. Therefore, in the nitrogen-doped porous carbon composite material, the precious metal elements have an extremely high atomic utilization rate. At the same time, in the nitrogen-doped porous carbon, the doping of nitrogen elements effectively regulates the electronic structure of the carbon material, promotes the interaction between the metal and the carbon, thereby enhancing the metal catalytic activity, so that the nitrogen-doped porous carbon material exhibits excellent catalytic performance, and can be well used as a catalyst in the fields of fuel cells, VOCs catalytic oxidation and water electrolysis.
[0028] In addition, in the preparation method of the nitrogen-doped porous carbon material described in the present invention, waste plastics are used as carbon sources and nitrogen sources, the carbon elements and nitrogen elements originally contained in the waste plastics are fully utilized, and the waste plastics are reacted with precious metal precursors through two heat treatments to obtain a nitrogen-doped porous carbon composite material. The prepared nitrogen-doped porous carbon composite material has a high loading amount of precious metals and a higher dispersion of precious metals. Therefore, the method described in the present invention not only realizes the resource recycling of waste plastics, but also uses waste plastics to prepare nitrogen-doped porous carbon composite materials with better performance. The nitrogen-doped porous carbon composite material can be used as a fuel cell catalyst, a VOCs catalytic oxidation catalyst and a water electrolysis catalyst, and all have excellent catalytic effects and have broad application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 This is a TEM mapping image of the Pt element in the nitrogen-doped porous carbon composite material prepared in Example 1. DETAILED DESCRIPTION
[0030] The specific implementation of the present invention is described in detail below in conjunction with the accompanying drawings. It should be understood that the specific implementation described here is only used to illustrate and explain the present invention, and is not used to limit the present invention.
[0031] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0032] In the present invention, the nitrogen-doped porous carbon composite material comprises nitrogen-doped porous carbon and a precious metal element loaded on the nitrogen-doped porous carbon; wherein the precious metal element is selected from one or more of Pt, Pd, Au, Ru and Ir.
[0033] In a preferred embodiment, the noble metal element is selected from Pt and / or Pd.
[0034] In the present invention, nitrogen-doped porous carbon is used as a loading matrix for precious metals. The doping of nitrogen elements can effectively change the intrinsic electronic structure of the carbon material, thereby promoting the interaction between the loaded precious metal and the carbon substrate, and anchoring the precious metal on the substrate. In addition, the nitrogen-doped porous carbon used in the present invention has a large specific surface area and a rich pore structure, which can provide more available positions for the loading of precious metals, further increase the content of the loaded precious metals, and make the loading dispersion of the precious metals better, so as to expose more active sites, thereby improving the utilization rate of precious metal atoms in the nitrogen-doped porous carbon composite material, reducing the amount of precious metal raw materials, and further reducing the preparation cost, laying a solid foundation for the industrial application of precious metal catalysts.
[0035] In the present invention, in the nitrogen-doped porous carbon composite material, the loading amount of precious metals is significantly increased, and the loading amount of the precious metal elements is 0.8-2.3wt%, preferably 1-2.3wt%. In the nitrogen-doped porous carbon composite material described in the present invention, the loading amount of precious metals is significantly higher than that of the prior art. By using the nitrogen-doped porous carbon described in the present invention as a substrate, the loading amount of precious metals on the substrate can be significantly increased, which helps to evenly disperse the loaded precious metals. Specifically, in the nitrogen-doped porous carbon composite material, the loading amount of the precious metal elements can be 0.8wt%, 1wt%, 1.2wt%, 1.4wt%, 1.8wt%, 2wt% or 2.3wt%.
[0036] In the present invention, the specific surface area of the nitrogen-doped porous carbon is 100-700 m 2 / g, in the nitrogen-doped porous carbon, the atomic percentage of nitrogen is 3-6at%. Preferably, the specific surface area of the nitrogen-doped porous carbon is 300-650m 2 / g. Specifically, the specific surface area of the nitrogen-doped porous carbon can be 100m 2 / g, 200m 2 / g、300m 2 / g, 400m 2 / g、500m 2 / g、600m 2 / g or 700m 2 / g; in the nitrogen-doped porous carbon composite material, the atomic percentage of nitrogen element can be 3at%, 4at%, 5at% or 6at%.
[0037] The present invention also provides a method for preparing the nitrogen-doped porous carbon composite material, the method comprising the following steps:
[0038] (1) crushing the waste plastic, and then mixing the obtained waste plastic particles with an optional nitrogen source for a heat treatment;
[0039] (2) The product obtained by heat treatment is mixed with a noble metal precursor solution, the mixed solution is then dried, and then the obtained dry product is subjected to secondary heat treatment.
[0040] In the method described in the present invention, waste plastics are used as carbon sources and nitrogen sources, and the carbon and nitrogen elements originally contained in the waste plastics are used to load the precious metal precursor by a method of two heat treatments to prepare a nitrogen-doped porous carbon composite material. The nitrogen atoms in the nitrogen-doped porous carbon composite material have a greater electronegativity than carbon atoms, which changes the electron distribution of the carbon base surface to a certain extent, promotes the anchoring of metal atoms, and the developed specific surface area provides sufficient distribution space for metal substances, thereby showing a performance that is beneficial to the loading of metal substances as a whole, so that the prepared material has excellent catalytic activity, and can be used as a catalyst in fuel cells, VOCs catalytic oxidation and electrolysis of water. In addition, more importantly, the present invention can realize the recycling and reuse of waste plastics by using waste plastics to prepare nitrogen-doped porous carbon composite materials, reduce the pressure of waste plastics on environmental pollution, and further open up a new way for the resource utilization of waste plastics, and provide a new idea. In addition, the method described in the present invention is simple in process, and a product with excellent performance can be prepared by two-step heat treatment, which has huge industrial application prospects.
[0041] In the present invention, the waste plastic is selected from one or more of waste polyurethane plastic, waste polyamide plastic and waste polyimide plastic, more preferably waste polyurethane plastic and / or waste polyamide plastic.
[0042] In a preferred embodiment, the particle size of the waste plastic particles is 10-150 μm, preferably 60-150 μm.
[0043] In a specific embodiment, the nitrogen source is selected from one or more of urea, melamine and ethylenediaminetetraacetic acid.
[0044] In the method of the present invention, the weight ratio of the waste plastic particles to the nitrogen source is 1:0.1-0.5. Specifically, the weight ratio of the waste plastic particles to the nitrogen source can be 1:0.1, 1:0.2, 1:0.3, 1:0.4 or 1:0.5.
[0045] In a specific embodiment, the primary heat treatment is performed in an inert gas. The inert gas refers to a gas that does not participate in the reaction during the reaction. In a specific embodiment, the inert gas is selected from at least one of nitrogen, argon and helium.
[0046] In a preferred embodiment, during the primary heat treatment, the ratio of the sum of the weights of the waste plastic particles and the nitrogen source to the flow rate of the inert gas is 1 g:90-110 mL / min.
[0047] In a specific embodiment, waste plastic and an optional nitrogen source are used for pyrolysis in step (1) to prepare a nitrogen-doped porous carbon material. In the present invention, by controlling the conditions of the primary heat treatment, the prepared nitrogen-doped porous carbon material can have a larger specific surface area and higher activity, which is more conducive to the subsequent loading of precious metals. Preferably, the conditions of the primary heat treatment include: a temperature of 750-900°C and a time of 4-5h. Specifically, the temperature of the primary heat treatment can be 750°C, 800°C, 850°C or 900°C; the time of the primary heat treatment can be 4h, 4.5h or 5h.
[0048] In a preferred embodiment, in step (2), the product obtained in step (1) is mixed with a noble metal precursor solution, and then dried and heat treated to effectively load noble metal elements on the nitrogen-doped porous carbon material. In the present invention, the noble metal precursor in the noble metal precursor solution is selected from at least one of a palladium precursor, a platinum precursor, a gold precursor, a ruthenium precursor and an iridium precursor, preferably a palladium precursor and / or a platinum precursor. In a specific embodiment, the palladium precursor may be ammonium chloropalladate, the platinum precursor may be potassium chloroplatinate, the gold precursor may be chloroauric acid, the ruthenium precursor may be ruthenium chloride, and the iridium precursor may be iridium chloride.
[0049] In the method described in the present invention, less precious metal precursor raw materials can be used for preparation, and the precious metal loading in the prepared nitrogen-doped porous carbon composite material is higher. The method described in the present invention can use less precious metal raw materials to prepare high-loaded nitrogen-doped porous carbon composite materials, and the prepared product has good dispersion of the loaded precious metals, which improves the atomic utilization rate of the active precious metals, further saves the preparation cost of the precious metal catalyst, and better solves the current problem of high preparation cost of precious metal catalysts.
[0050] In a preferred embodiment, the weight ratio of the noble metal precursor to the waste plastic particles is 0.008-0.1:1, more preferably 0.01-0.05:1. Specifically, the weight ratio of the noble metal precursor to the waste plastic particles can be 0.01:1, 0.05:1, 0.1:1, 0.15:1 or 0.2:1.
[0051] In the present invention, by controlling the conditions of the secondary heat treatment in step (2), the loading amount of precious metal elements in the prepared nitrogen-doped porous carbon composite material can be further increased, and the dispersion of precious metal elements in the subsequently prepared nitrogen-doped porous carbon composite material is better, making the performance of the material more superior. Preferably, the conditions of the secondary heat treatment include: a temperature of 650-850°C and a time of 3.5-4.5h. Specifically, the temperature of the secondary heat treatment can be 650°C, 700°C, 750°C, 800°C or 850°C; the time of the secondary heat treatment can be 3.5h, 3.8h, 4h or 4.5h.
[0052] In a preferred embodiment, during the primary heat treatment and the secondary heat treatment, the heating rate is 1-20°C / min, preferably 5-15°C / min. Specifically, the heating rate may be 1°C / min, 5°C / min, 8°C / min, 10°C / min, 12°C / min, 15°C / min, 18°C / min or 20°C / min.
[0053] The present invention also provides a nitrogen-doped porous carbon composite material prepared by the above method, wherein the noble metal loading in the material is significantly higher than that in the prior art, and the noble metal loaded has good dispersibility, which is more conducive to improving the catalytic activity of the prepared material. Therefore, the prepared nitrogen-doped porous carbon composite material can be widely used as a catalyst in the fields of fuel cells, VOCs catalytic oxidation and water electrolysis, and can have excellent activity.
[0054] The present invention will be described in detail below through examples, but the protection scope of the present invention is not limited thereto.
[0055] The experimental methods in the following examples, unless otherwise specified, are all conventional methods in the art. The experimental materials used in the following examples, unless otherwise specified, are all commercially available.
[0056] Example 1
[0057] (1) The waste polyamide plastic is dried at 100° C., then crushed and sieved to obtain waste polyamide plastic particles with a particle size of 20-120 μm, then the waste polyamide plastic particles and the nitrogen source ethylenediaminetetraacetic acid are stirred and mixed at a weight ratio of 1:0.5, and then the mixed material is subjected to a heat treatment in nitrogen at a temperature of 900° C. for 0.5 h, a heating rate of 10° C. / min, and a ratio of the total amount of the waste polyamide plastic particles and the nitrogen source to the flow rate of the nitrogen gas flow of 1 g:100 ml / min;
[0058] (2) The product obtained in step (1) is immersed in a potassium chloroplatinate solution (the weight ratio of the waste polyamide plastic to potassium chloroplatinate is 1:0.02), and then the material is dried and placed in a tubular furnace for secondary heat treatment. The temperature of the secondary heat treatment is 800°C and the time is 1 hour. After the heat treatment, a nitrogen-doped porous carbon composite material is obtained.
[0059] Example 2
[0060] (1) drying the waste polyurethane plastic at 100° C., crushing and sieving to obtain waste polyurethane plastic particles with a particle size of 20-120 μm, and then subjecting the waste polyurethane plastic particles to a heat treatment in nitrogen at a temperature of 780° C. for 0.5 h and a heating rate of 10° C. / min. The ratio of the total amount of the waste polyurethane plastic particles and the nitrogen source to the flow rate of the nitrogen gas flow is 1 g:100 ml / min;
[0061] (2) The product obtained in step (1) is immersed in a chloropalladic acid ammonium solution (the weight ratio of the waste polyurethane plastic to chloropalladic acid is 1:0.03), and then the material is dried and placed in a tubular furnace for secondary heat treatment. The temperature of the secondary heat treatment is 700°C and the time is 1 hour. After the heat treatment, a nitrogen-doped porous carbon composite material is obtained.
[0062] Example 3
[0063] (1) The waste polyurethane plastic is dried at 100° C., then crushed and sieved to obtain waste polyurethane plastic particles with a particle size of 20-120 μm, and then the waste polyurethane plastic particles are subjected to a heat treatment in nitrogen at a temperature of 750° C. for 0.5 h, a heating rate of 10° C. / min, and a ratio of the total amount of the waste polyurethane plastic particles and the nitrogen source to the flow rate of the nitrogen gas flow of 1 g:100 ml / min;
[0064] (2) The product obtained in step (1) is immersed in a potassium chloroplatinate solution (the weight ratio of the waste polyurethane plastic particles to potassium chloroplatinate is 1:0.05), and then the material is dried and placed in a tubular furnace for secondary heat treatment. The temperature of the secondary heat treatment is 650°C and the time is 1 hour. After the heat treatment, a nitrogen-doped porous carbon composite material is obtained.
[0065] Comparative Example 1
[0066] The method of Example 1 was followed, except that during the preparation process, the waste polyamide plastic was replaced with an equal weight of polyethylene plastic, and no additional nitrogen source was added for preparation.
[0067] Comparative Example 2
[0068] The method of Example 2 is followed, except that the temperature of the first heat treatment is 700°C and the temperature of the second heat treatment is 600°C.
[0069] Comparative Example 3
[0070] The method of Example 2 is followed, except that the temperature of the first heat treatment is 950°C and the temperature of the second heat treatment is 900°C.
[0071] Comparative Example 4
[0072] The method of Example 2 is followed, except that the temperature of the first heat treatment is 950°C, and the temperature of the second heat treatment is 880°C.
[0073] Comparative Example 5
[0074] The method of Example 2 is followed, except that the temperature of the first heat treatment is 930°C and the temperature of the second heat treatment is 600°C.
[0075] Comparative Example 6
[0076] The method of Example 2 is followed, except that the temperature of the first heat treatment is 780°C and the temperature of the second heat treatment is 600°C.
[0077] Comparative Example 7
[0078] The method of Example 2 is followed, except that the temperature of the first heat treatment is 700°C and the temperature of the second heat treatment is 650°C.
[0079] Test Case
[0080] Test Example 1
[0081] The nitrogen-doped porous carbon composite material prepared in Example 1 was subjected to TEM mapping test using TEM energy spectrum. The results are as follows: Figure 1 shown.
[0082] As can be seen from the figure, the noble metal in the nitrogen-doped porous carbon composite material prepared in Example 1 is uniformly distributed on the surface of the nitrogen-doped carbon material in nanometer size and is evenly dispersed.
[0083] Test Example 2
[0084] The specific surface areas of the materials prepared in Examples 1-3 and Comparative Examples 1-7 were tested using BET, and the test results are shown in Table 1;
[0085] XPS was used to test the atomic percentage of N element in the materials prepared in Examples 1-3 and Comparative Examples 1-7. The test results are shown in Table 1.
[0086] ICP-MS was used to test the content of precious metal elements in the materials prepared in Examples 1-3 and Comparative Examples 1-7. The test results are shown in Table 1.
[0087] Table 1
[0088] Example No. <![CDATA[Specific surface area m 2 / g]]> N doping amount at% Precious metal content wt% Example 1 701 4.8 0.9 Example 2 763 5.2 2.1 Example 3 724 3.9 1.5 Comparative Example 1 530 0.6 0.1 Comparative Example 2 416 2.8 0.26 Comparative Example 3 539 8.2 0.36 Comparative Example 4 692 3.5 0.32 Comparative Example 5 685 4.5 0.41 Comparative Example 6 550 4.8 0.56 Comparative Example 7 520 3.5 0.48
[0089] It can be seen from the results in Table 1 that the nitrogen-doped porous carbon composite material of the present invention has a higher noble metal loading, and the noble metal loaded is more evenly dispersed, which improves the atomic utilization rate of the noble metal, and the loaded metal activity is higher, which enhances the catalytic activity of the material, and can be widely used as a catalyst in fuel cells, VOCs catalytic oxidation and water electrolysis, showing great industrialization potential. In addition, the method described in the present invention can also realize the resource recycling of waste plastics, providing a new way for the recycling of waste plastics.
[0090] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.
Claims
1. A nitrogen-doped porous carbon composite material, characterized in that: The nitrogen-doped porous carbon composite material comprises nitrogen-doped porous carbon and a noble metal element loaded on the nitrogen-doped porous carbon; Wherein, the noble metal element is selected from one or more of Pt, Pd, Au, Ru and Ir; The specific surface area of the nitrogen-doped porous carbon is 100-700 m 2 / g, in the nitrogen-doped porous carbon, the atomic percentage of nitrogen element is 3-6at%; In the nitrogen-doped porous carbon composite material, the loading amount of the noble metal element is 0.8-2.3 wt %.
2. A method for preparing a nitrogen-doped porous carbon composite material, characterized in that: The method comprises the following steps: (1) crushing the waste plastic, and then mixing the obtained waste plastic particles with an optional nitrogen source for a heat treatment; (2) mixing the product obtained by the heat treatment with a noble metal precursor solution, then drying the mixed solution, and then subjecting the obtained dry product to a secondary heat treatment; The conditions of the primary heat treatment include: a temperature of 750-900°C and a time of 0.5-3h; The conditions of the secondary heat treatment include: temperature of 650-850°C and time of 0.5-3h; The waste plastic is selected from one or more of waste polyurethane plastic, waste polyamide plastic and waste polyimide plastic; The noble metal precursor in the noble metal precursor solution is selected from at least one of a palladium precursor, a platinum precursor, a gold precursor, a ruthenium precursor and an iridium precursor.
3. The method according to claim 2, characterized in that The particle size of the waste plastic particles is 10-150 μm.
4. The method according to claim 2, characterized in that: In step (1), the primary heat treatment is performed in an inert gas; Preferably, the inert gas is selected from at least one of nitrogen, argon and helium; Preferably, during the primary heat treatment, the ratio of the sum of the weights of the waste plastic particles and the nitrogen source to the flow rate of the inert gas is 1 g:90-110 mL / min.
5. The method according to claim 2, characterized in that: The weight ratio of the noble metal precursor to the waste plastic particles is 0.008-0.1:
1.
6. The method according to claim 2, characterized in that The nitrogen source is selected from one or more of urea, melamine and ethylenediaminetetraacetic acid.
7. The method according to claim 2 or 6, characterized in that: The weight ratio of the waste plastic particles to the nitrogen source is 1:0.1-0.
5.
8. The method according to claim 2, characterized in that: During the primary heat treatment and the secondary heat treatment, the heating rate is 1-20° C. / min.
9. The nitrogen-doped porous carbon composite material prepared according to the method of any one of claims 2 to 8.
10. Use of the nitrogen-doped porous carbon composite material according to any one of claims 1 or 9 in the preparation of fuel cell catalysts, water electrolysis catalysts or VOCs catalytic oxidation catalysts.
Citation Information
Patent Citations
Preparing method for nitrogen-doped porous carbon material, catalyst comprising material and application of material
CN104689857A
Transitional metal oxide / nitrogen-doped ordered mesoporous carbon composite material and preparation method thereof
CN108840370A
Preparation technology of nitrogen-doped mesoporous carbon composite metal oxide electrode material for supercapacitor
CN108878176A
Nitrogen-doped ruthenium-based biochar catalyst, preparation method and application thereof
CN108927194A
Selective hydrogenation catalyst for unsaturated ketone and preparation method and application thereof
CN108940346A